Effect of Organisational Foresight Capabilities on Business Survival in the UAE Banking Sector – The Mediating Effect of Innovation - ALQASEM, MURAD MOHAMMAD (2024)
Purpose: This study aims to investigate the effects of organisational foresight capabilities on the survival of businesses within the United Arab Emirates (UAE) banking sector, with explorative and exploitative innovations serving as mediators. Design/ methodology/ approach: The conceptual framework is based on dynamic capability theory and contingency theory. It includes three foresight capabilities: perceiving, prospecting, and probing as antecedents of business survival, which have direct effects and indirect effects via explorative and exploitative innovations. The study employed quantitative methods to examine various hypotheses using primary data collected in July, August, and September 2022 through an adapted well-structured questionnaire. The population included 1914 employees in managerial positions in the UAE banking sector, and the final dataset comprises 388 subjects. Findings: First, explorative innovation has a higher impact on business survival compared to exploitative innovation. Second, explorative innovation and exploitative innovation partially mediate the relationship between perceived organisational foresight capabilities and business survival. Third, explorative innovation and exploitative innovation partially mediate the relationship between prospecting organisational foresight capabilities and business survival. Fourth, explorative innovation and exploitative innovation fully mediate the relationship between probing and business survival. Research limitations/ Implications: First, the study provides theoretically enriching and meaningful insights into organisational foresight capabilities as a new taxonomy by investigating individually its three dimensions (perceiving, prospecting, and probing) in relation to business survival. Second, it captures the distinct influence of innovation by investigating both the explorative and exploitative aspects, which contributes to reducing ambiguity and enhancing comprehension of the innovation concept. Third, the paper offers valuable contextual contribution by introducing new empirical evidence from an area predominantly overlooked, specifically focusing on the UAE. Originality/ value: The importance of this study lies in its focus on integrating organisational foresight, innovation, and business survival. Business survival is rarely investigated, and the results from the UAE are valuable for the empirical understanding of organisational foresight. Keywords: Organisational Foresight, Perceiving, Prospecting, Probing, Explorative Innovation, Exploitative Innovation, Business Survival.